2009
DOI: 10.1002/smll.200900358
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Forces and Their Uses in Self‐Assembly

Abstract: The ability to assemble nanoscopic components into larger structures and materials depends crucially on the ability to understand in quantitative detail and subsequently "engineer" the interparticle interactions. This Review provides a critical examination of the various interparticle forces (van der Waals, electrostatic, magnetic, molecular, and entropic) that can be used in nanoscale self-assembly. For each type of interaction, the magnitude and the length scale are discussed, as well as the scaling with par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
1,437
3
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,427 publications
(1,483 citation statements)
references
References 279 publications
(423 reference statements)
28
1,437
3
15
Order By: Relevance
“…nearly 70 times larger than that of latex beads), meaning AuNPs experience much stronger attractive van der Waals force at the same distance. 41 While surface capping improves colloidal stability, the native AuNP surface is masked.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…nearly 70 times larger than that of latex beads), meaning AuNPs experience much stronger attractive van der Waals force at the same distance. 41 While surface capping improves colloidal stability, the native AuNP surface is masked.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…To date, a few reviews have discussed nanoparticle superlattices,1, 2, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 however, a dedicated review emphasizing the important roles of soft ligands has not yet reported to the best of our knowledge. We therefore are motivated to cover the recent advances in nanoparticle superlattices from viewpoint of soft ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Today, nano-particles can be synthesized with a variety of shapes [1][2][3][4][5] and arrangements [6,7], allowing for different applications. To unveil the full potential of these nano-particle based applications [8,9] in general, it is imperative to understand and characterize the wide range of intriguing properties of these nanoscale entities.…”
Section: Introductionmentioning
confidence: 99%